Use of Creative Writing to Develop a Semantic Differential Tool for Assessing Soundscapes - Welch, David; Shepherd, Daniel; Dirks, Kim; Tan, Mei Yen; Coad, Gavin (Frontiers in Psychology, 2019)
Exploring our understanding of soundscapes to understand why and how sound impacts people is important. The aim of this study was to develop a short quantitative questionnaire that would use terms generated by creative writers to assess people’s experiences of a soundscape. This process may provide different items for the questionnaire and thus, potentially, different dimensions or fuller definitions of dimensions that have already been identified. In the preliminary phase, a group of people identifying themselves as good writers listened to recordings of natural, traffic, and human sound environments and wrote about their impressions and responses to each. Qualitative analysis was used to extract themes from the writing. These themes were identified by key words, and scalar items were developed to form a short 17-item questionnaire. The questionnaire was administered to 228 people in Auckland City, New Zealand, with participants recruited from city streets and in a central-city park. Respondents were comfortable to use the questionnaire. Factor analysis revealed patterns of responding with five dimensions: Calming, Protecting, Hectic, Belonging, and Stability. There were correspondences between these and others previously reported in the literature, as well as differences. The use of items derived from creative writing provided interesting insights into the soundscape, including spirituality, the sense of time passing, and physical wellbeing. The park soundscape was measurably better than the street soundscapes on all dimensions, and streets with less vehicular traffic tended to be experienced as more Calming and Protecting, and less Hectic. This implies that there is validity in the scales generated. In future, it would be valuable to test the questionnaire in more varied environments, to add greater variability to the soundscapes.